The association between social integration and neighborhood dissatisfaction and unsafety: a cross-sectional survey study among social housing residents in Denmark - Abirami Srivarathan; Maria Kristiansen; Terese Sara Høj Jørgensen; Rikke Lund (BMC, 2022)
Abstract Background Social integration and perceived neighborhood environment are recognized as important social determinants of health. However, little is known about the association between social integration and perceived neighborhood environment among underrepresented population groups, such as residents in disadvantaged neighborhoods, in public health research. The aim of this study is to: 1) Describe the levels of social integration and 2) Investigate the association between social integration and neighborhood dissatisfaction and unsafety among middle-aged and older social housing residents. Methods A multilingual face-to-face interviewer-administrated survey questionnaire was conducted among 206 residents aged 45 years and above (response rate: 34.1%) of various nationalities in disadvantaged socioeconomic positions in a social housing area in Denmark. The assessment of social integration was based on cohabitation status, frequency of face-to-face and non-face-to-face interaction with social relations and participation in local association activities. Neighborhood dissatisfaction measured the level of dissatisfaction with the neighborhood, and neighborhood unsafety assessed the level of unsafety being outdoors in the neighborhood. Descriptive statistics were conducted to illustrate respondent characteristics and the distribution of social integration among the study population. Logistic regression models were applied to analyze associations between social integration and neighborhood dissatisfaction and unsafety, adjusted for age, sex, country of origin, educational attainment and employment status. Results In total, 23.8% of the respondents reported low levels of social integration. A medium level of social integration was associated with higher odds of neighborhood dissatisfaction (OR: 2.36; 95% CI: 1.04-5.38) compared to the highest level of integration. A low frequency of face-to-face interaction was associated with higher odds of neighborhood dissatisfaction (OR: 2.65; 95% CI: 1.16-6.06) and neighborhood unsafety (OR: 2.41; 95% CI: 1.04-5.57) compared to the highest frequency of face-to-face interaction. Conclusions Almost one-fourth of respondents reported low levels of social integration. A medium level of social integration was associated with neighborhood dissatisfaction. A low frequency of face-to-face interaction was associated with neighborhood dissatisfaction and unsafety. The results suggest that targeted health promotion interventions designed to foster face-to-face interaction, hold potential to reduce neighborhood dissatisfaction and unsafety among residents in disadvantaged neighborhoods.